Efektifitas Pemberdayaan Keluarga Terhadap Kontrol Metabolik Pada Pasien Diabetes Mellitus Tipe 2 - Rasnah, Rasnah; Sjattar, Elly L; Yusuf, Saldy (Jurnal Keperawatan Muhammadiyah, 2019)
Background : Family empowerment plays an important role in the management of diabetes mellitus experienced by family members. Because of the chronic nature of this disease, people with diabetes mellitus need long-term assistance to improve self-care and delay chronic complications from diabetes mellitus through glycemic control. Aim : To conduct a systematic review and assess the effectiveness of family empowerment for metabolic control in patients with type 2 diabetes mellitus. Method : Systematic reviews are carried out using electronic databases in article searches such as PubMed, ScienceDirect, ProQuest, Google Scholar. Results: After reviewing five articles it was found that family-based intervention or by empowering families in the care of patients with diabetes mellitus played a role in decreasing HbA1c as an indicator in glycemic control. And the most widely used instruments are the scale of self-care and diabetes activity (SDSCA), the diabetes empowerment scale (DES) and the diabetes knowledge questionnaire (DKQ). Conclusion : From the review of the article reviewed it can be concluded that families must be involved in the care of people with diabetes mellitus, diabetes education given only to individuals with type 2 diabetes limits the impact on patients, therefore empowering families will provide a large role in the management of chronic diseases that emphasize context where this disease occurs including the family's physical environment, education, and the personal needs of patients and family members. Helps develop healthy family behavior and shows self-management of diabetic patients, especially in health care programs, especially those who are able to promote various forms of social support, glycemic control and to strengthen ties between family members.Keywords : Family empowerment, metabolic control, type 2 diabetes mellitus.